Synthesis and anion binding properties of phthalimide-containing corona[6]arenes - Gu, Meng-Di; Lu, Yao; Wang, Mei-Xiang (Beilstein Journal of Organic Chemistry, 2019)
Functionalized O6-corona[3]arene[3]tetrazines were synthesized efficiently and conveniently by means of a macrocyclic condensation reaction between N-functionalized 3,6-dihydroxyphthalimides and 3,6-dichlorotetrazine under mild conditions in a one-pot reaction manner. The novel macrocycles exist as a mixture of rapidly interconvertible conformers in solution while in the solid state they adopt the conformation in which three phthalimide units are cis,trans-orientated. Acting as electron-deficient macrocyclic hosts, the synthesized O6-corona[3]arene[3]tetrazines self-regulated conformational structures to complex anions in the gas phase and in the solid state owing to the anion–π noncovalent interactions between anions and the tetrazine rings.
Keywords: anion–π interactions; coronarenes; host–guest complexation; N-functionalized phthalimides; O6-corona[3]arene[3]tetrazines